A 3D-printed capacitive smart insole for plantar pressure monitoring - Samarentsis, A. G.; Makris, G.; Spinthaki, S.; Christodoulakis, G.; Tsiknakis, M.; Pantazis, A. K. (Sensors, 2022)
Gait analysis refers to the systematic study of human locomotion and finds numerous applications in the fields of clinical monitoring, rehabilitation, sports science and robotics. Wearable sensors for real-time gait monitoring have emerged as an attractive alternative to the traditional clinical-based techniques, owing to their low cost and portability. In addition, 3D printing technology has recently drawn increased interest for the manufacturing of sensors, considering the advantages of diminished fabrication cost and time. In this study, we report the development of a 3D-printed capacitive smart insole for the measurement of plantar pressure. Initially, a novel 3D-printed capacitive pressure sensor was fabricated and its sensing performance was evaluated. The sensor exhibited a sensitivity of 1.19 MPa'-1, a wide working pressure range (<872.4 kPa) , excellent stability and durability (at least 2.280 cycles), great linearity (R'2=0.993), fast response/recovery time (142-160 ms), low hysteresis (DH<10%) and the ability to support a broad spectrum of gait speeds (30-70steps/min). Subsequently, 16 pressure sensors were integrated into a 3D-printed smart insole that was successfully applied for dynamic plantar pressure mapping and proven able to distinguish the various gait phases. We consider that the smart insole presented here is a simple, easy to manufacture and cost-effective solution with the potential for real-world applications.